Conceptualizing the personal outcomes of information - J. Kari (Information Research: An International Electronic Journal)
Introduction. This paper conceptualizes the outcomes of information as an analytical construct that synthesizes different understandings of information use. The article focuses on the perspective of the individual person. Method. The discussion is primarily based on peer-reviewed articles and monographs in the whole field of information science. The items were normally selected from the Library and Information Science Abstracts database by the keywords 'outcomes', 'uses' and 'effects' of information. Analysis. Outcome of information is first defined as anything that ensues from the individual's assimilation of a message. The outcomes are then analysed hierarchically by dividing them into categories which are further divided into subcategories, until a concrete enough level is reached. Results. The main types of information outcome are information use and effect of information, and their most prominent common dimension is apparently mental vs. physical outcomes. As a result of the scrutiny, a taxonomy of information outcomes is presented in a conceptual model. Conclusion. The model is also a conceptual map of the research area, and indicates a certain imbalance in our knowledge of information outcomes. The model is detailed enough to enable a deductive mode of inquiry, but inductive approaches ought also to be cultivated.